(untitled) (Research, Society and Development, 2020)
The aim of the review was to verify serum vitamin D levels in children and adolescents with asthma. The study is an integrative review, with 14 articles selected from the PubMed, ScienceDirect and VHL databases from 2013 to 2017. The studies analyzed revealed that individuals with asthma mostly have deficiency or insufficiency in serum levels. D. Children and adolescents with asthma had lower vitamin D levels than healthy subjects. Thus, it was evidenced that serum vitamin D was lower among asthmatics, with studies showing a significant association between vitamin D levels and the presence of pathology.